The increased antioxidant action of HDL is independent of HDL cholesterol plasma levels in triple-negative breast cancer - Campos, Amarilis de Lima; Sawada, Maria Isabela Bloise Alves Caldas; Santana, Monique Fátima de Mello; Iborra, Rodrigo Tallada; de Assis, Sayonara Ivana Santos; Reis, Mozania; de Carvalho, Jacira Xavier; Gebrim, Luiz Henrique; Passarelli, Marisa (Frontiers in Oncology, 2023)
The association between high-density lipoprotein cholesterol (HDLc) with the incidence and progression of breast cancer (BC) is controversial. HDL removes excess cholesterol from cells and acts as an antioxidant and anti-inflammatory. BC is a heterogeneous disease, and its molecular classification is important in the prediction of clinical and therapeutic evolution. Triple-negative breast cancer (TNBC) presents higher malignancy, lower therapeutic response, and survival rate. In the present investigation, the composition and antioxidant activity of isolated HDL was assessed in women with TNBC compared to controls. Twenty-seven women with a recent diagnosis of TNBC, without prior treatment, and 27 healthy women (control group) paired by age and body mass index (BMI) were included in the study. HDL and Low-density lipoprotein (LDL) were isolated from plasma by discontinuous density gradient ultracentrifugation. Plasma lipid profile and HDL composition (total cholesterol, TC; triglycerides, TG; HDL cholesterol, HDLc; phospholipids, PL) were determined by enzymatic colorimetric methods. ApoB and apo A-I were quantified by immunoturbidimetry. The antioxidant activity of HDL was determined by measuring the lag time phase for LDL oxidation and the maximal rate of conjugated dienes formation in LDL incubated with copper sulfate solution. The absorbance (234 nm) was monitored for 4 h, at 3 min intervals. The control group was similar to the TNBC concerning menopausal status, concentrations, and ratios of plasma lipids. The composition of the HDL particle in TC, TG, PL, and apo A-I was also similar between the groups. The ability of HDL to retard LDL oxidation was 22 % greater in the TNBC group as compared to the control and positively correlated with apoA-I in HDL. Moreover, the antioxidant activity of HDL was greater in the advanced stages of TNBC (stages III and IV) compared to the control group. The maximum rate of formation of conjugated dienes was similar between groups and the clinical stages of the disease. The results highlight the role of HDL as an antioxidant defense in TNBC independently of HDLc plasma levels. Improved antioxidant activity, reflected by retardation of conjugated oxidation in LDL, could contribute to limiting oxidative and inflammatory stress in TNBC in advanced stages.